2007
DOI: 10.1002/pon.1261
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplant depression as risk factor for survival of patients undergoing allogeneic haematopoietic stem cell transplantation

Abstract: Depression is probably not a simple indicator of a worse health status. Further research is needed to decide if depression must be considered as an independent risk factor for survival when diagnosed in the pre-transplant period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…In the field of transplantation research, four papers have shown the impact of depressive symptoms on mortality after kidney [6,23], heart [24] or allogenic hematopoietic stem cell [7] transplantation. This relationship consistently caused higher mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of transplantation research, four papers have shown the impact of depressive symptoms on mortality after kidney [6,23], heart [24] or allogenic hematopoietic stem cell [7] transplantation. This relationship consistently caused higher mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms can predict the medical outcome of numerous conditions, including cardiovascular diseases, diabetes mellitus, chronic obstructive pulmonary disease, as well as kidney transplantation, heart transplantation or allogenic hematopoietic stem cell transplantation [4][5][6][7]. Depressive symptoms have been consistently shown to be associated with higher mortality.…”
Section: Introductionmentioning
confidence: 99%
“…28 The Hospital Anxiety and Depression Scale assesses psychologic well-being 29,30 ; it was specifically developed for patients with physical illnesses and has been extensively used in the setting of cancer treatment, including HSCT patients. 31 The POMS (35 items) was used to assess 4 separate subscale scores for depression, anger/hostility, vigor, and fatigue 32 and has been widely used in the assessment of mood changes resulting from a variety of interventions, including exercise trials, and also in HSCT. 33 The National Comprehensive Cancer Network DistressThermometer 34 used consists of a visual analog scale from 0 to 10 and a 34-item dichotomy problem list.…”
Section: Data Collection and Endpointsmentioning
confidence: 99%
“…Unfortunately, again they subsequently did not recognize these, and other factors (for example, see Grulke et al 10 ), as important confounders. The authors did adjust their models for sex, marital status and educational level which are inadequate as proxies for important lifestyle factors.…”
mentioning
confidence: 99%